2021
DOI: 10.1002/cam4.4468
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies for hepatocellular carcinoma

Abstract: Cases of hepatocellular carcinoma (HCC) are rapidly rising. This is particularly the case in the Western world, as a result of increasing rates of chronic liver disease, secondary to lifestyle‐associated risk factors and the lack of an established screening programme for the general population. Traditionally, radical/curative treatment options for HCC, including liver transplantation and surgical resection are reserved for the minority of patients, presenting with an early stage cancer. For patients with advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 136 publications
(591 reference statements)
0
22
0
1
Order By: Relevance
“… 9 Among these regimens, lenvatinib seemed to be the most commonly used regimen for the patients in clinical practice. Unfortunately, similar to the clinical activity of PD-1 inhibitors monotherapy clinically (ORR <20%), 10 the ORR of lenvatinib monotherapy was also disappointing clinically (ORR <30%), 22 which highlighted the necessity to investigate new combination regimens to expand the potential patients who might benefit from lenvatinib-based administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Among these regimens, lenvatinib seemed to be the most commonly used regimen for the patients in clinical practice. Unfortunately, similar to the clinical activity of PD-1 inhibitors monotherapy clinically (ORR <20%), 10 the ORR of lenvatinib monotherapy was also disappointing clinically (ORR <30%), 22 which highlighted the necessity to investigate new combination regimens to expand the potential patients who might benefit from lenvatinib-based administration.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the physiological role of liver in processing extraneous drugs and the first-pass metabolism, HCC might naturally exhibit a relatively immunosuppressed state that was heavily regulated by the immune system, which suggested that immunotherapy (PD-1 blockades) might play a pivotal role to reverse the process in the tumor and help T cells to kill the tumor cells. 10 Consequently, the potential significance of PD-1 blockades in HCC had been proved by pembrolizumab, nivolumab, and camrelizumab as second-line treatment in China based on the results of Phase II clinical trials. 11 Unfortunately, the ORR of the PD-1 blockades monotherapy among patients with HCC ranged from 15–20% and all the PD-1 blockades failed to improve OS ultimately, which highlighted that immune checkpoint inhibitor-based regimens might be of potential significance for patients with unresectable HCC clinically.…”
Section: Introductionmentioning
confidence: 99%
“…La inmunoterapia ha cambiado el panorama del tratamiento de pacientes con tumores sólidos recurrentes y con metástasis, tales como melanoma maligno y cáncer de pulmón de células no pequeñas [27,28]. La aplicación de los regímenes de inmunoterapia en CHC, con resultados excelentes en términos de seguridad y eficacia, ha revolucionado el tratamiento de estos pacientes.…”
Section: Inmunoterapiaunclassified
“…Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and the third leading cause of cancer-related mortality worldwide [ 1 ]. Immunotherapy is a systemic treatment option, with immune checkpoint inhibitors such as tyrosine kinase inhibitors (e.g., lenvatinib, cabozantinib, regorafenib) and anti-angiogenic monoclonal antibodies (ramucirumab) [ 2 , 3 , 4 ]; however, the response to ICIs is only 20–30% of patients [ 5 ]. Surgical resection is a curative treatment option which is currently chosen first for HCC [ 6 ]; however, up to 70% of patients who undergo surgical resection may experience recurrence of HCC, which can affect their long-term prognosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%